Mycotoxin-contaminated diets and an adsorbent affect the performance of Nellore bulls finished in feedlots - Custodio, L. [UNESP]; Prados, L. F.; Figueira, D. N. [UNESP]; Yiannikouris, A.; Gloria, E. M.; Holder, V. B.; Pettigrew, J. E.; Santin, E.; Resende, F. D. [UNESP]; Siqueira, G. R. [UNESP] (Elsevier, 2020)
Mycotoxins are present in almost all feedstuffs used in animal nutrition but are often ignored in beef cattle systems, even though they can affect animal performance. The objective of this study was to evaluate the effects of mycotoxins and a mycotoxin adsorbent (ADS) on performance of Nellore cattle finished in a feedlot. One hundred Nellore cattle (430 ± 13 kg) were used in a randomized complete block design with a 2 × 2 factorial arrangement of treatments. The factors consisted of two diets with either natural contamination (NC) or exogenous contamination (EC) and the presence (1 g/kg of DM; ADS) or absence of a mycotoxin adsorbent. The NC and EC diets had the following contaminations, respectively: 0.00 and 10.0 μg/kg aflatoxins, 5114 and 5754 μg/kg fumonisins, 0.00 and 42.1 μg/kg trichothecenes B, 0.00 and 22.1 μg/kg trichothecenes A and 42.9 and 42.9 μg/kg fusaric acid. At the beginning of the experiment, all animals were weighed, and four randomly selected animals were slaughtered to evaluate the initial carcass weight. After 97 days of treatment, all animals were weighed and slaughtered. There was no interaction among factors for the DM intake (DMI; P = 0.92); however, there was a tendency for the EC diets to decrease the DMI by 650 g/day compared to animals fed NC diets (P = 0.09). There was a trend for interaction among factors (P = 0.08) for the average daily gain (ADG), where the greatest ADG was observed for cattle fed the NC diet (1.77 kg), and the lowest was observed for those fed the EC diet (1.51 kg). The NC + ADS and EC + ADS treatments presented intermediate values for ADG. The animals fed the NC diet had a greater final BW (596 kg) than animals fed the EC treatment (582 kg; P = 0.04). There was a tendency for interaction among factors for carcass gain (P = 0.08). Similarly to ADG, the highest carcass gain was observed for animals fed the NC diet (1.20 kg), and the lowest was observed for those fed the EC diet (1.05 kg). The NC + ADS and EC + ADS treatments presented intermediate values. The natural contamination groups had greater carcass gain than that of the EC groups, and the use of the ADS recovered part of the weight gain in animals fed the EC diet. In conclusion, mycotoxins at the levels evaluated affected the performance of beef cattle, and adsorbents may mitigate their impact.
Keywords: aflatoxins; carcass; fumonisins; fungi; mycotoxin production